Semantically enhanced version of a research article from PLoS Neglected Tropical Diseases: Impact of environment and social gradient on leptospira infection in urban slums - Shotton, D; Miles, A; Klyne, G; Portwin, K (Image Bioinformatics Research Group, Department of Zoology, 2008)
Semantic enhancement: The semantic enhancements to the original PLoS NTD paper by Reis et al (2008) were created by David Shotton, Alistair Miles, Graham Klyne and Katie Portwin, Image Bioinformatics Research Group, Department of Zoology, University of Oxford. This enhanced version of the paper was published on 3 September 2008 at doi:10.1371/journal.pntd.0000228.x001. Explanation of semantic enhancements: A paper by Shotton et al. (2009) describing the full range of semantic enhancement applied to the Reis et al. (2008) article has been submitted for publication; a preprint of this paper is available at http://purl.org/net/semanticpublication/Shotton_et_al_PLoS_enhancement_report.pdf. A wider review of the current state and potential usefulness of semantic publication is given in a separate paper (Shotton, 2009) to appear in the April 2009 issue of Learned Publishing; a preprint of that paper is available at http://purl.org/net/semanticpublication/Shotton_Semantic_publishing_evaluation.pdf. A description of the technical implementation of these semantic enhancements is given by Shotton and Portwin (2009) at doi:10.1371/journal.pntd.0000228.x009. A separate annotation guidelines document (Portwin and Shotton, 2009; doi:10.1371/journal.pntd.0000228.x010) describes the heuristics applied when deciding which textual terms were to be assigned to the semantic classes highlighted in the text of the enhanced version of the Reis et al. (2008) article.